A radiographic and anthropometric study of the effect of a contoured sandal and foot orthosis on supporting the medial longitudinal arch - Escalona-Marfil, Carles (BioMed Central, 2014)
BACKGROUND: In-shoe foot orthoses improve conditions such as plantar heel pain (fasciitis), probably due to their ability to raise the medial longitudinal arch of the foot and lower the stress on the plantar tissues. Increasingly the arch-profile form of the in-shoe foot orthosis is being incorporated into sandal footwear, providing an alternative footwear option for those who require an orthosis. The purpose of this study was to evaluate if a sandal that incorporates the arch-profile of an in-shoe foot orthosis does indeed raise the medial longitudinal arch. METHODS: Three commercially available non-medical devices (contoured and flat sandal, prefabricated in-shoe orthosis) worn by healthy individuals were studied in two independent experiments, one using radiographic measurements in Australia (n = 11, 6 female, age 26.1 ± 4.3 yrs, BMI 22.0 ± 2.4 kg/m(2)) and the other utilising anthropometric measures in the USA (n = 10, 6 female, age 26.3 ± 3.8 yrs, BMI 23.5 ± 3.7 kg/m(2)). A barefoot condition was also measured. Dorsal arch height was measured in both experiments, as well as in subtalar neutral in the anthropometric experiment. One way repeated measures ANOVA with follow up Bonferroni-corrected pairwise comparisons were used to test differences between the conditions (contoured and flat sandal, orthosis, barefoot). Mean difference and 95% confidence intervals (CI) and standardised mean differences (SMD) were also calculated. RESULTS: The contoured sandal significantly increased dorsal arch height compared to barefoot and flat sandal in both the anthropometric and radiographic experiments with SMD ranging from 0.95 (mean difference 5.1 mm (CI: 0.3, 1.6)) to 1.8 (4.3 mm (1.9, 6.6)). There were small differences between the contoured sandal and orthosis of 1.9 mm (0.6, 3.3) in the radiographic experiment and 1.2 mm (−0.4, 0.9) in the anthropometric experiment. The contoured sandal approximated the subtalar neutral position (0.4 mm (−0.5, 0.7)). CONCLUSIONS: Medial longitudinal arch height is elevated by contoured sandals and approximates subtalar joint neutral position of the foot and that achieved by an orthosis. Practitioners wanting to increase the medial longitudinal arch can do so with either an orthosis or a contoured sandal that includes the raised arch profile form of an orthosis.